About ecology in heritage protection - Lukšionytė, Nijolė (Journal of Architecture and Urbanism, 2013)
Houses from natural or recycled materials, heated by natural energy represent green building or sustainable architecture. In the wider context, the conception of ecology is applicable not only for a separate house, but also for the all town planning and architecture. This article is meant to describe several relevant ways to implement sustainable development in the historical territories of Lithuanian cities by seeking for a dialog between contemporary needs and the policy of sustainability.In 2008 the European Union has initiated a purposeful document – “2030 Heritage Strategy”. There is declared a holistic preservation of vital cultural heritage and its surroundings by comprehending, controlling, conserving and restoring it properly and promoting the appreciation of heritage as a cultural treasure of all the urban community. The document encourages arranging and reusing the existing buildings by invoking the innovative technologies.There are a lot of deserted, unused buildings in the historical territories of Lithuanian cities. First thing that should be done is to give the status of revitalization priority zone for the territories of historical surrounding. The revitalization would proceed by reaching for the balance between preservation of the existing resources and inserting new functions and elements. Obviously, the notification of revitalization zone will not take an effect itself – the changes have to be initiated. Therefore the governance of revitalization zones is so important.The specific field that waits impatiently for a “green” treatment is the old wooden houses of Lithuanian cities and towns. People often forget that a timber house, though not new, is itself a base of healthy microclimate. There would be enough to take care of suitable ways of heating and trimming and we would have an ecologic house. This would open a new field for architects’ activity.In 2011 by the support of Kaunas City Municipality there has been started a database of Kaunas wooden architecture, which can already be used through a website (www.archimede.lt). Here a professional documentation of wooden architecture is being accumulated. It is expected that through this website the information will reach the house owners, administration of subdistricts and municipalities and gradually the understanding of the value of wooden architecture will be developed. We think that an educative support could grow into particular social solidarity program: people would share their knowledge and experience and a community interested in preservation of wooden houses would come into being.Article in Lithuanian.Apie ekologiją paveldosaugojeSantrauka. Straipsnyje apibūdinamos ekologiško požiūrio į paveldo priežiūrą gairės Lietuvos miestų istorinėse teritorijose. Daugelyje tarptautinių dokumentų deklaruojamas holistinis gyvybingo kultūros paveldo išsaugojimas ragina ieškoti dialogo tarp šiuolaikinių poreikių ir tausojimo politikos. Lietuvos miestų istorinėse dalyse daug apleistų pastatų. Tokioms teritorijoms straipsnyje siūloma suteikti atgaivinimo (revitalizacijos) prioriteto zonų statusą. Būtina jų kaitos priežiūra – istorinių zonų valdymo organizavimas. Ekologiško būsto resursus smarkiai praplėstų tinkamai prižiūrimi senieji mediniai namai. 2011 m. pradėtoje kurti Kauno medinės architektūros duomenų bazėje kaupiama profesionali medinių pastatų dokumentacija. Tikimasi, kad per tinklalapį bus ugdomas medinės architektūros vertės supratimas, skatinantis jungtis į jos išsaugojimu suinteresuotą bendruomenę.Reikšminiai žodžiai: tausojimas, atgaivinimas (revitalizacija), istorinės teritorijos, miestų mediniai namai.